Promoting EFL Students’ Academic Character through Instructional Practice in Revolution Industry 4.0 - Hadiyanto Hadiyanto (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThis study investigates English as a Foreign Language (EFL) teachers' instructional practices in developing students' academic character. Self-evaluation questionnaires were distributed to 37 teachers, and 26 were returned. Seven Focus Group Discussion (FGD) participants were selected based on their availability. The study reveals that EFL teachers averagely facilitated students to enhance their academic character and rated developing students' academic character at a critical level. There are five majors handicap for EFL teachers in developing students' academic character.  First, the curriculum does not integrate the academic character with the courses offered. Second, implementing academic character into the curriculum is time-consuming. Besides, teachers assume that their students can automatically apply academic character in their life without it should be integrated into the courses. Lastly, the teaching loads that teachers must do are enormous. Drawing from those problems, several recommendations are proposed: curriculum policy at the university level should be taken, providing a standard syllabus application, providing a simple evaluation system, and freeing EFL teachers from bureaucratic and administrative burdens. Furthermore, the current study has sounded the research result to university academic authority and recommended that the department embed students' academic character in learning and suggested the EFL teachers embed and assess students' academic character development through instructional practices.AbstrakStudi ini menyelidiki praktik instruksional guru English as a Foreign Language (EFL) dalam mengembangkan karakter akademik siswa. Kuesioner evaluasi diri dibagikan kepada 37 guru, dan 26 dikembalikan. Tujuh peserta Focus Group Discussion (FGD) dipilih berdasarkan ketersediaan mereka. Studi ini mengungkapkan bahwa guru EFL rata-rata memfasilitasi siswa untuk meningkatkan karakter akademis mereka dan menilai pengembangan karakter akademis siswa pada tingkat kritis. Ada lima jurusan yang menjadi kendala bagi guru EFL dalam mengembangkan karakter akademik siswa. Pertama, kurikulum tidak mengintegrasikan karakter akademik dengan mata kuliah yang ditawarkan. Kedua, menerapkan karakter akademik ke dalam kurikulum memakan waktu. Selain itu, guru beranggapan bahwa siswanya dapat secara otomatis menerapkan karakter akademik dalam kehidupannya tanpa perlu diintegrasikan ke dalam mata pelajaran. Terakhir, beban mengajar yang harus dilakukan guru sangat besar. Berangkat dari permasalahan tersebut, beberapa rekomendasi diusulkan: kebijakan kurikulum di tingkat universitas harus diambil, penyediaan penerapan silabus yang standar, penyediaan sistem evaluasi yang sederhana, dan membebaskan guru EFL dari beban birokrasi dan administrasi. Selanjutnya, penelitian ini telah menjajaki hasil penelitian kepada otoritas akademik universitas dan merekomendasikan agar departemen tersebut menanamkan karakter akademik siswa dalam pembelajaran dan menyarankan guru EFL untuk menanamkan dan menilai pengembangan karakter akademik siswa melalui praktik pembelajaran.How to Cite:  Hadiyanto. (2020).  Promoting EFL Students' Academic Character Through Instructional Practice in Revolution Industry 4.0. TARBIYA: Journal of Education in Muslim Society, 7(2), 167-182. doi:10.15408/tjems.v7i2.18998.